The Impact of Various Diets on the Management of Patients with Type 1 Diabetes - systematic review - Kacalak, Mateusz (Quality in Sport, 2025)
Introduction: Type 1 diabetes (T1D) is a chronic autoimmune disorder characterized by the destruction of pancreatic β-cells, leading to absolute insulin deficiency. Given the increasing global incidence—especially among children and adolescents—growing attention is being paid not only to pharmacological treatment but also to the supportive role of targeted nutritional interventions. Aim of the study: This study aims to present and compare the effects of selected dietary models on glycemic control, the risk of complications, and the quality of life in patients with T1D. Materials and Methods: A narrative review was conducted based on scientific literature published between 2023 and 2025, sourced from the PubMed database. The analysis focused on five dietary patterns: plant-based, Mediterranean, gluten-free, ketogenic, and low-FODMAP diets. Conclusions: Diets rich in fiber, unsaturated fats, and low-glycemic-index foods may significantly improve glycemic stability, reduce inflammation, and positively influence gut microbiota composition in patients with T1D. Each dietary approach demonstrates distinct therapeutic potential and should be individually tailored. Dietary therapy should be recognized as an integral component of a multidisciplinary approach to T1D management.